Integrasi Nilai-Nilai Islam dalam Budaya Sekolah sebagai Upaya Pembentukan Karakter Siswa: Studi Kajian Pustaka - Riska Ninda; Siti Bashirah; Murniati Wahab; Mustain Billah Talamoa (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Student character should be strengthened by instilling values that emphasize moral and spiritual dimensions in addition to academics, in line with the demands of the times and changes in society in education. One strategy to create a learning environment that can shape students' character comprehensively is by integrating Islamic teachings into school culture. The aim of this study is to see how Islamic principles are applied in school culture, how they are implemented in the classroom, and how they affect students' character development. This study analyzes various literature, including scientific papers related to the research problem, using a library research method. The findings show that regular religious activities, role modeling by teachers, the implementation of Islamic principles in education, and creating a school environment that supports character development are ways Islamic values are integrated into school culture. Student character traits such as being religious, disciplined, responsible, tolerant, and socially caring are partly shaped through this integration. Thus, an Islamic-based school culture can be used as a teaching strategy in an ongoing process to develop students' moral character.